ACUPUNCTURE AND BEE VENOM THERAPY IN THE CHRONIC LOW BACK PAIN: A SHORT REVIEW - Lucache, Beatrice; Albu, Elena; Mungiu, Ostin C (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Many pharmacological and nonpharmacologic therapies are available for the treatment of the low back pain (LBP). Despite medications are the most frequently prescribed therapy for LBP, the use of various complementary medicine techniques is increasing. The paper summarizes the latest evidence on the treatment of musculoskeletal conditions (with special focus on chronic LBP) by using acupuncture and bee venom therapy (BVT). Methodology: The overview is based on English-language studies and articles found by searches of Medline over more than last 10 years. All the paper found that refer to LBP and at least one of the analyzed therapies have been taken into account. Results: The mechanism of action, efficiency, harms, toxicity and contraindications are highlighted for the two therapies. The literature on these topics is extensive and controversial. There are trials in favour of using the two complementary therapies for rheumatic diseases, as well trials arguing that the observed analgesic effects are related to a strong placebo response. Conclusions: The choice of using acupuncture and BVT for chronic LBP depends on various factors related to patient features and preferences, but nowadays an increased attention and support has to be noted.